Pengaruh Public Service Motivation Terhadap Kinerja Pegawai Melalui Kepuasan Kerja Pegawai Di Puskesmas Rawat Inap Kota Yogyakarta - Winarsih, Trisni (208-7721)
The research took a topic the influence of public service motivation towards the employeeesâ performance through performance job satisfaction of the employees at hospital care of public health center of Yogyakarta City. The topic chosen is set out from the researcherâs curiousness to know whether exthant influence of public service motivation toward the employeesâ performance throug job satisfaction. In order that the researcher proposed hypothesis of public service motivation through job influence positively toward the employeeâs performance.The research was conducted in three (3) hospital care of public health center of Yogyakarta City. The research took primary data by distributing response questionnaire of the responden toward public service motivation and job satisfaction to whole employees performance in three hospital health service. Secondary data of the employees performance in three hospital care of public health service was taken from job assessment that was conducted by Badan Kepegawaian Daerah for each semester. Number or sampel in the research was as many 178Â  people, with cencus method. Analysis used was Structural equation Modeling (SEM) by using Analysis of Moment Structure program version 22,0 and SPSS 20,0From the analysis result conducted revealed that Public Service Motivation through job satisfaction influences positively toward performance. And Public Service MotivationÂ  does not influence positively toward performance.